Analysis of Profits and Break Even Point of Jamnapari Goat Farming - Niuzi Khan; Mehmood Hussein (Newinera Publisher, 2021)
This study discusses profits and break even point of jamnapari goat farming. Goat and sheep husbandry offers an excellent image that may demonstrate how it might promote a wide range of economic activity. Goats are simple to breed, need little initial capital, require little animal feed, and are easily adapted to their surroundings. The goat is a kind of animal that provides many advantages to the society. Goats are an alternate source of revenue for goat farming businesses looking to expand their operations. The Jamnapari Crossbred goat is a kind of indigenous goat that has strong development potential and may help to boost the income of the surrounding area's farmers. Diversification (multi-commodity farming) is an alternative to carrying out business efficiency on relatively fixed land areas while increasing productivity.